On mx-ωb-Open Sets - B. Jubair, Waqas; J. Ali, Haider (Al-Nahrain Journal of Science, 2022)
In this paper, we shall use the m-structure topological spaces to introduce new concept, which is the -ω-open set. Several facts, results and examples are given to illustrate our work.